Oviposition deterrent and ovicidal activities of seven herbal essential oils against female adults of housefly, Musca domestica L. - Sinthusiri, Jirisuda; Soonwera, Mayura (My University, 2014)
The oviposition deterrent and ovicidal of seven herbal essential oils derived from Citrus sinensis, Cymbopogon citratus, Eucalyptus glubulus, Illicium verum, Lavandula angustifolia, Mentha piperita, and Zingiber cussumunar were assessed against the gravid female of housefly, Musca domestica L., under laboratory conditions and compared with commercial insecticide (10 % w/v cypermethrin). They were assayed at three concentrations (1.0, 5.0, and 10.0 %) where plastic cups containing 1 ml of desired oil concentration and cotton pad soaked with 10 ml of milk solution (10 % w/v) were used as oviposition substrate. The 0.1 ml of deferent concentrations was dropped on ten housefly eggs, which were used for ovicidal activity. The number of eggs laid and the hatched larvae in each cup was recorded to evaluate the oviposition deterrent and ovicidal activities of the herbal essential oils. High concentration (10 %) of herbal essential oils showed high percent effective repellency (ER). The 10 % I. verum oil caused complete oviposition deterrence (100 % ER, oviposition activity index (OAI)=-1.0), followed by Z. cussumunar, M. piperita, L. angustifolia, C. citratus, C. sinensis, and E. glubulus oils with 97.20, 88.55, 88.14, 87.93, 76.68, and 57.00 % ER, respectively. As the concentration of herbal essential oils increased from 1.0, 5.0, and up to 10.0 % concentration, the hatching rate decreased. Ten percent I. verum oil gave the maximum inhibiting rate at 97.3 % (LC50 value of 6.85 %); in addition, the other herbal essential oils showed the minimum inhibiting rate of 3.3-22.7 %. On the other hand, cypermethrin 10 % w/v showed complete oviposition deterrence (100 % ER, OAI=-1.0) and ovicidal activity (100 % inhibiting rate). Our data showed that I. verum oil have high potential of oviposition deterrence and ovicide housefly control. © 2014 Springer-Verlag.
Keywords: Essential oil; Housefly; Musca domestica; Ovicidal activities; Oviposition deterrent